2014
DOI: 10.1200/jco.2014.56.7743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 30-Day Hospital Readmission After Surgery for Advanced-Stage Ovarian Cancer in a Medicare Population

Abstract: Purpose To analyze rate, risk factors, and costs associated with 30-day readmission after ovarian cancer surgery. Patients and Methods The SEER-Medicare linked database (1992 to 2010) was used to evaluate readmission rates within 30 days of index surgery in patients with stage IIIC/IV ovarian, primary peritoneal, or fallopian tube cancer. Multivariable logistic regression was used to identify factors associated with readmission. Results Of 5,152 eligible patients, 1,003 (19.5%) were readmitted within 30 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
4
25
1
Order By: Relevance
“…23 In addition to the morbidity experienced during the hospitalization, complications that develop during hospitalization for medical and surgical treatment can also result in rehospitalization for the patient. 15,24 In this context, the patients with comorbidity should be carefully examined preoperatively, so as to identify any potential intervention that may decrease their risk for postoperative complications during rehospitalization. In addition, the patient should be cautiously observed during the postoperative hospitalization to ensure that they are fully ready for discharge before their release from the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 In addition to the morbidity experienced during the hospitalization, complications that develop during hospitalization for medical and surgical treatment can also result in rehospitalization for the patient. 15,24 In this context, the patients with comorbidity should be carefully examined preoperatively, so as to identify any potential intervention that may decrease their risk for postoperative complications during rehospitalization. In addition, the patient should be cautiously observed during the postoperative hospitalization to ensure that they are fully ready for discharge before their release from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…17,20,22,24 In the study conducted by Alhilli et al, 17 it was seen that patients undergoing rehospitalizations experienced more than 1 series admission. Those patients were diagnosed with ovarian cancer with a rate of 57%, cervix with 30%, and uterus with 11%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Eskander et al reported a SEER review of rehospitalizations following surgery for ovarian cancer in the United States [14]. The goal behind using SEER data is to generate more generalizable results, but specific patient and tumor related data is not available for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Eskander's SEER study is notable for the increase in re-hospitalization rates over time, associated with a corresponding decrease in length of stay (LOS) over time [14]. Another study in the gynecology oncology population of patients suggested that LOS could be safely decreased with an overall 5% readmission rate [24].…”
Section: Discussionmentioning
confidence: 99%